Overexpression of EPS8 is associated with poor prognosis in patients with acute lymphoblastic leukemia. Issue 6 (June 2015) - He, Ying-zhi; Liang, Zhao; Wu, Mei-rong; Wen, Qi; Deng, Lan; Song, Chao-yang; Wu, Bing-yi; Tu, San-Fang; Huang, Rui; Li, Yu-hua
Highlights: Expression of EPS8, MDR1, and WT1 in ALL generally evolved in parallel. Patients with EPS8, MDR1, or WT1 high expression showed a higher risk of relapse. Patients with high EPS8, WT1 or MDR1 expression had shorter DFS. Patients expressing high- EPS8 / WT1 / MDR1 profile has the worst clinical outcome. Abstract: Molecular markers have become an invaluable tool in monitoring disease status particularly of leukemias, as bone marrow samples can be easily collected for analysis during all stages of disease development including diagnosis, treatment, and follow-up. Two genes that have been used as prognostic markers in acute leukemia are Wilms' tumor (WT1) and multidrug resistance-1 (MDR1). A novel gene, epidermal growth factor receptor pathway substrate 8 (EPS8), is often over-expressed and associated with poor outcome in some solid tumor types. However, whether EPS8 is also associated with the development of acute lymphoblastic leukemia (ALL) is unclear. Here, quantitative real-time PCR was used to evaluate the expression of EPS8, MDR1, and WT1 in bone marrow samples of adult ALL patients ( n  = 107) and non-leukemia controls ( n  = 22). EPS8, MDR1, and WT1 were detected in ALL patients, and significant correlations were found between expression profiles for EPS8 and MDR1, EPS8 and WT1, and MDR1 and WT1 . In general, high expression of EPS8, MDR1, or WT1 in patients was associated with a higher risk of relapse. Furthermore, when patients were stratified based on high or low expression of the genes, Kaplan–Meier survival analysis indicated that disease-free survival of patients with the high-EPS8/high-WT1/high-MDR1 profile was significantly shorter than in patients with the low-EPS8/low-WT1/low-MDR1 profile or those excluded from either of these groups ( P  < 0.0001). Thus, EPS8, as MDR1 and WT1, may be a clinically valuable biomarker for assessing the outcome of ALL patients.